Influencing Factors and Multiple Paths of Entrepreneurship in High-Tech Enterprises: A Fuzzy-Set Qualitative Comparative Analysis of Configuration - Liyan Zhang; Yuting Wang (Discrete Dynamics in Nature and Society)
This paper selects 93 high-tech enterprises listed in 2019 in China’s A-share market and comprehensively integrates six variables on three levels, namely, internal guarantee, internal incentives, and external institutions, through fuzzy-set qualitative comparative analysis (fsQCA). On this basis, a discussion was conducted about the multiple concurrent factors and various paths stimulating entrepreneurship. The results show that (1) a single factor does not necessarily lead to high entrepreneurship; (2) high entrepreneurship could be stimulated by four paths: driving mechanism with salary incentive as the core and market mechanism as the support, driving mechanism with government intervention and market mechanism as synergistic drivers, driving mechanism with equity and control power as dual drivers under external institutions, and driving mechanism with external institutions and internal incentives as joint drivers; (3) market competition plays an indispensable role in stimulating entrepreneurship, while management capability suppresses entrepreneurship; (4) nonhigh entrepreneurship could be generated by five paths, which are asymmetric relative to the configurations of high entrepreneurship.